Liquid crystal composition and liquid crystal display device thereof

By developing a liquid crystal composition containing the general formula F, general formula RM and general formula SA compounds, the problem of cumbersome PI alignment layer process in the production of PSA liquid crystal displays is solved, and the vertical alignment and efficient display of liquid crystal molecules are achieved, thereby improving the Productivity and display quality.

CN116064053BActive Publication Date: 2025-02-07JIANGSU HECHENG DISPLAY TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202111284847.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-01
Publication Date
2025-02-07
Estimated Expiration
2041-11-01

AI Technical Summary

Technical Problem

In the production process of existing PSA LCDs, there are problems such as cumbersome, complex and time-consuming PI alignment layer processes, resulting in low production efficiency and high cost, and are prone to poor display problems such as uneven display, image stickiness and broken highlights.

Method used

Develop a liquid crystal composition comprising at least one compound of general formula F, at least one polymerizable compound of general formula RM and at least one self-aligning agent of general formula SA, through the combination of these compounds, the verticality of the liquid crystal molecules is achieved. Alignment, no PI alignment layer is required.

Benefits of technology

It realizes that the liquid crystal display device has a small rotation viscosity, low residue concentration, good pretilt angle stability and small stability while maintaining appropriate clear points, optical anisotropy and dielectric anisotropy absolute values. The surface roughness of the polymer layer improves contrast and response speed, and solves problems such as uneven display and broken highlights.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116064053B_ABST
    Figure CN116064053B_ABST
Patent Text Reader

Abstract

The present invention provides a liquid crystal composition and a liquid crystal display device thereof. The liquid crystal composition of the present invention has an appropriate clearing point, an appropriate optical anisotropy, an appropriate absolute value of dielectric anisotropy, a larger K value, a smaller rotational viscosity, a smaller concentration of residues, a better pre-tilt angle stability, and a smaller surface roughness of the polymer layer, so that the liquid crystal display device containing the liquid crystal composition has a higher contrast, a faster response speed, and can achieve vertical alignment of liquid crystal molecules without a PI alignment layer while maintaining an appropriate temperature use range and an appropriate threshold voltage, and can effectively accelerate the production process of PSA-type liquid crystal displays, increase production efficiency, and can effectively improve problems such as "image stickiness", uneven display, "broken bright spots" and the like existing in existing PSA-type liquid crystal displays, and has a high practical application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of liquid crystals, in particular to a liquid crystal composition and a liquid crystal display device comprising the liquid crystal composition. Background Art

[0002] Liquid crystal display (LCD) has achieved rapid development due to its small size, light weight, low power consumption and excellent display quality, and has been widely used in portable electronic information products. According to the type of display mode, LCD can be divided into PC (phase change), TN (twist nematic), STN (super twisted nematic), ECB (electrically controlled birefringence), OCB (optically compensated bend), IPS (in-plane switching), FFS (fringe field switching), VA (vertical alignment) and PSA (polymer stable alignment).

[0003] The liquid crystal display element contains a nematic liquid crystal composition, and the liquid crystal composition has appropriate characteristics. By improving the characteristics of the liquid crystal composition, an AM element with good characteristics can be obtained. The relationship between the characteristics of the liquid crystal composition and the AM element is summarized in the following Table A. The characteristics of the liquid crystal composition are further described based on commercially available AM ​​elements. The temperature range of the nematic phase is related to the temperature range of the element. The viscosity of the liquid crystal composition is related to the response time of the element. In order to make the element display dynamic images, it is preferred that the response time of the element is short.

[0004] Table A Characteristics of liquid crystal composition and AM element

[0005] serial number Characteristics of Liquid Crystal Compositions Characteristics of AM components 1 Nematic phase has a wide temperature range Wide temperature range 2 Low viscosity Short response time 3 Large optical anisotropy High contrast 4 The absolute value of dielectric anisotropy is large Low threshold voltage, low power consumption, high contrast 5 Larger specific resistance High voltage holding rate and contrast ratio 6 UV and heat stable Long life 7 Large elastic constant High contrast, short response time, fast response speed

[0006] In the application of liquid crystal display devices, the contrast has a critical impact on visual effects. Generally speaking, the greater the contrast, the clearer and more eye-catching the image, and the brighter the color; on the contrary, if the contrast is small, the whole picture will be gray. High contrast is of great help to the clarity, detail and grayscale performance of the image. High-contrast products have advantages in black and white contrast, clarity, integrity and other aspects. Contrast also has a great impact on the display effect of dynamic video. Since the light and dark conversion in dynamic images is relatively fast, the higher the contrast, the easier it is for the human eye to distinguish such a conversion process.

[0007] In order to improve the response speed of liquid crystal display devices, it is necessary to reduce the rotational viscosity of liquid crystal materials as much as possible. However, generally, low-viscosity liquid crystal materials have lower clearing points and optical anisotropy, so when formulating liquid crystal compositions, it is necessary to consider other performance requirements while reducing the viscosity.

[0008] The PSA type liquid crystal display mode is to add a small amount (for example, 0.3wt%, more typically, <1wt%) of one or more polymerizable compounds to the liquid crystal composition, which can ensure that after the liquid crystal composition is filled into the liquid crystal box, the liquid crystal molecules are polymerized in situ (usually by UV light polymerization) or cross-linked in a state with an initial orientation when a voltage is applied between the electrodes or when no voltage is applied, thereby fixing the orientation of the liquid crystal molecules. With the continuous development of PSA type liquid crystal display elements, they are applied to various traditional liquid crystal display devices, such as the known PSA-VA, PSA-OCB, PSA-IPS, PSA-FFS and PSA-TN type liquid crystal displays. In a PSA type liquid crystal display, a liquid crystal composition containing a polymerizable compound is located between two substrates, each substrate is equipped with an electrode structure, or two electrode structures are placed on only one of the substrates. In addition, either or both of the two substrates may contain an alignment layer disposed on the substrate or the electrode structure (if present) to induce the initial alignment of the liquid crystal composition. Like conventional liquid crystal displays, PSA type liquid crystal displays can be operated as active matrix displays or passive matrix displays. In the case of active-matrix displays, the individual pixels are addressed by means of integrated non-linear active elements, such as transistors; in the case of passive-matrix displays, the individual pixels are usually addressed according to multiplexing methods known in the art.

[0009] After the liquid crystal composition is filled into the display device, the polymerizable compounds contained in the liquid crystal composition are usually polymerized or crosslinked in situ by UV photopolymerization, wherein the UV photopolymerization is achieved by exposing the liquid crystal composition to UV radiation (preferably, while applying a voltage to the electrode structure). As a result of UV exposure, the polymerized or crosslinked polymerizable compounds are phase separated from other compounds in the liquid crystal composition and form a polymer layer on the surface of the substrate, where they cause a pre-tilt angle of the liquid crystal molecules relative to the substrate. For PSA-VA, PSA-OCB, PSA-FFS and PSA-TN type liquid crystal displays, the polymerization of the polymerizable compounds is preferably carried out under the application of voltage; for PSA-IPS displays, it is possible to apply a voltage or not, preferably without applying a voltage.

[0010] Generally, in the production method of PSA type liquid crystal display, UV photopolymerization is achieved through the following two steps:

[0011] In the first step (hereinafter referred to as the "UV1 step"), the liquid crystal composition is exposed to UV radiation (hereinafter referred to as "UV1 radiation") emitted by a radiation source (hereinafter referred to as the "light source"), and a voltage is applied to the electrode structure, thereby generating a pre-tilt angle. The more preferred polymerizable compound should generate a smaller pre-tilt angle in the same time or generate the same pre-tilt angle in a shorter UV1 radiation time (i.e., a faster angular velocity) to improve production efficiency, shorten the tact time during mass production, and reduce costs; at the same time, the faster the angular velocity of the polymerizable compound, the more conducive it is to achieve complete polymerization of the polymerizable compound, thereby reducing polymer residue. In order to increase the angular velocity, it is preferred to use UV1 radiation with a shorter wavelength; and in order to increase the voltage holding ratio (Voltage Holding Ratio, VHR), it is preferred to use UV1 radiation with a longer wavelength. Therefore, it is usually difficult to take into account both a faster angular velocity and a higher voltage holding ratio.

[0012] In the second step (hereinafter referred to as "UV2 step"), the liquid crystal composition is exposed to UV radiation (hereinafter referred to as "UV2 radiation") without applying voltage to the electrode structure to ensure that the residual polymerizable compound that has not been polymerized in the UV1 step can be completely polymerized. It is expected that after the UV2 step, the change in the pre-tilt angle is as small as possible to reduce the possibility of uneven display caused by the non-uniformity of the UV process (non-uniform external conditions such as light, heat, stress, etc.) of the PSA type liquid crystal display. At the same time, the intensity of UV radiation in the UV2 step should be reduced to avoid or reduce negative effects (such as reduced reliability or image stickiness).

[0013] In the current production of PSA-type liquid crystal displays, it is necessary to coat a layer of polyimide (PI) alignment layer (PI alignment layer for short) on the glass substrate to achieve vertical alignment of liquid crystal molecules, but this method has obvious shortcomings (such as the PI coating process is cumbersome, complicated, and time-consuming), and there are many other adverse effects, which greatly limit the quality of liquid crystal displays. The PI alignment process greatly reduces production efficiency and increases production costs; at the same time, due to the limited ability to accurately control the PI printing area, and the deviation of the PI printing area will affect the sealant sealing of narrow-frame products and the display effect of the edge, it greatly limits the development of current mainstream narrow-frame products and greatly reduces the yield rate of its production. In the prior art, the use of the PI alignment layer is mainly replaced by adding a self-aligning agent to the liquid crystal composition, but not all liquid crystal compositions can be perfectly matched with polymerizable compounds and self-aligning agents. After the UV1 step and the UV2 step, there may be problems such as residues of polymerizable compounds and self-aligning agents, slow angular velocity of the pre-tilt angle, and uneven surface of the polymer layer. At the same time, the poor miscibility of the liquid crystal composition and the polymerizable compound will result in poor rigidity of the polymer network formed after the polymerization of the polymerizable compound, which will cause the structure of the polymer network to change when the PSA-type liquid crystal display element displays the same pattern continuously for a long time, and then cause the pre-tilt angle of the liquid crystal molecules to change, resulting in poor display.

[0014] In addition, the liquid crystal compound still has some disadvantages in its application in PSA type liquid crystal displays after being mixed with a polymerizable compound and a self-aligning agent. The liquid crystal composition formed by the combination of the liquid crystal compound with the selected polymerizable compound and the self-aligning agent is required to have a lower rotational viscosity and good optoelectronic properties to achieve the expected display effect. The length of the polymerization process of the polymerizable compound directly affects the time required for the preparation process of the liquid crystal display element or the liquid crystal display device, but under normal circumstances, if the polymerization speed is too fast, large-particle polymers are easily formed, which easily causes poor displays such as "broken bright spots". Due to the uneven size of the polymer particles, the distribution of the polymer is also uneven, which in turn causes the problem of uneven display. Therefore, the problem that still needs to be solved is: to make the liquid crystal composition have a faster polymerization speed, uniform polymer particles (that is, smaller surface roughness of the polymer layer), and improved poor display problems such as "image viscosity", uneven display, "broken bright spots", etc."

[0015] In addition, with the development of display technology, the liquid crystal display industry has stricter requirements on the display quality of LCDs, especially in the TV industry. As TV sizes generally increase, LCD generation lines also increase, and the difficulty of manufacturing large-size LCD panels also increases significantly. Therefore, how to ensure display quality is an urgent problem to be solved. At the same time, in addition to continuously optimizing the panel manufacturing process, the development of liquid crystal materials is also one of the solutions. Especially for PSA-type liquid crystal displays, the selection of liquid crystal compositions used in combination with polymerizable compounds has become a research hotspot.

[0016] Therefore, the research focus in this field is to develop liquid crystal materials with fast polymerization speed, controllable polymerization process and good comprehensive performance to meet the needs of PSA type liquid crystal display elements, and to provide display technology that can achieve vertical alignment of liquid crystal molecules without the need for a PI alignment layer. Summary of the invention

[0017] Purpose of the invention: In view of the defects of the prior art, the purpose of the present invention is to provide a liquid crystal composition, which has a smaller residue concentration, better pre-tilt angle stability, and smaller polymer layer surface roughness while maintaining an appropriate clearing point, an appropriate optical anisotropy, an appropriate absolute value of dielectric anisotropy, a larger K value and a smaller rotational viscosity.

[0018] Another object of the present invention is to provide a liquid crystal display device comprising the liquid crystal composition.

[0019] Technical solution: In order to achieve the above invention objectives, the present invention provides a liquid crystal composition, the liquid crystal composition comprising:

[0020] At least one compound of the general formula F

[0021]

[0022] At least one polymerizable compound of the general formula RM

[0023] as well as

[0024] At least one self-aligning agent of the general formula SA

[0025]

[0026] in,

[0027] R F1 represents -H, halogen, a straight or branched alkyl group containing 1 to 12 (e.g., 2, 3, 4, 5, 6, 7, 8, 9, 10, or 11) carbon atoms, One or more non-adjacent -CH2- in a linear or branched alkyl group containing 1 to 12 carbon atoms may be independently replaced by -C≡C-, -O-, -CO-, -CO-O- or -O-CO-, and one or more -H in a linear or branched alkyl group containing 1 to 12 carbon atoms may be independently replaced by -F or -Cl;

[0028] R F2 Indicates that one or two or more non-adjacent -CH2- are independently replaced by -S- or -O- One or more rings with single bonds replaced by double bonds -O(CH2)n F4 OR F3 or

[0029] R F3 represents a straight or branched chain alkyl group containing 1 to 4 carbon atoms;

[0030] R1 represents -H, halogen, -CN, -Sp2-P2, a linear or branched alkyl group containing 1 to 12 (e.g., 2, 3, 4, 5, 6, 7, 8, 9, 10, or 11) carbon atoms, A straight or branched alkyl group containing 1 to 12 carbon atoms, One or more non-adjacent -CH2- may be independently replaced by -CH=CH-, -C≡C-, -O-, -CO-, -CO-O- or -O-CO-, and one or more -H may be independently replaced by -F or -Cl;

[0031] R S1 Indicates -Sp 1 -P 1 , a linear or branched alkyl group containing 1 to 12 (e.g., 2, 3, 4, 5, 6, 7, 8, 9, 10, or 11) carbon atoms, wherein one or more non-adjacent -CH2- in a straight-chain or branched alkyl group containing 1 to 12 carbon atoms can be independently replaced by -CH=CH-, -C≡C-, -O-, -CO-, -CO-O- or -O-CO-, and wherein a straight-chain or branched alkyl group containing 1 to 12 carbon atoms, One or more -H in can be independently replaced by -F or -Cl;

[0032] ring and ring Each independently expresses in One or more -CH2- in the ring may be replaced by -O-, and one or more single bonds in the ring may be replaced by double bonds, wherein One or more -H in the ring may be independently replaced by -CN, -F or -Cl, and one or more -CH= in the ring may be replaced by -N=;

[0033] ring and ring Each independently expresses in One or more -CH2- in the ring may be replaced by -O-, and one or more single bonds in the ring may be replaced by double bonds, wherein One or more -H in the group may be replaced independently by -F, -Cl, -CN, -Sp3-P3, a halogenated or unhalogenated straight-chain alkyl group containing 1 to 12 carbon atoms, a halogenated or unhalogenated straight-chain alkoxy group containing 1 to 11 carbon atoms, substituted, and -CH= in one or more rings may be replaced by -N=;

[0034] ring express in One or more -H in the group may be replaced independently by -F, -Cl, -CN, -Sp3-P3, a halogenated or unhalogenated straight-chain alkyl group containing 1 to 12 carbon atoms, a halogenated or unhalogenated straight-chain alkoxy group containing 1 to 11 carbon atoms, substituted, and -CH= in one or more rings may be replaced by -N=;

[0035] ring express in One or more -CH2- in the ring may be replaced by -O-, and one or more single bonds in the ring may be replaced by double bonds;

[0036] Ls1 and Ls3 each independently represent -F, -Cl, -CN, -NO2, -NCO, -NCS, -OCN, -SCN, -C(O)N(R S0 )2. -C(O)R S0 , a straight or branched alkyl group containing 1 to 12 (e.g., 2, 3, 4, 5, 6, 7, 8, 9, 10, or 11) carbon atoms, wherein one or more non-adjacent -CH2- in a straight-chain or branched alkyl group containing 1 to 12 carbon atoms can be independently replaced by -CH=CH-, -C≡C-, -O-, -CO-, -CO-O- or -O-CO-, and wherein a straight-chain or branched alkyl group containing 1 to 12 carbon atoms, One or more -H in the above-mentioned may be independently replaced by -F, wherein R S0 represents a straight or branched alkyl group containing 1 to 12 (e.g., 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12) carbon atoms;

[0037] Ls2 means -Sp 3 -P 2 or

[0038] R S2 and R S3 Each independently represents an anchoring group, the anchoring group is Where * indicates the connection site in the bonded structure;

[0039] p represents 1 or 2, wherein when p represents 2, -Sp 8 -X 2 Can be the same or different;

[0040] o means 0 or 1;

[0041] M S1 express

[0042] I S1 and J S1 Each independently represents -CH2-, -O- or -S-;

[0043] N S1 Indicates =O or =S;

[0044] V K1 、V K2 and V K3 Each independently represents -CH= or -N=;

[0045] X 1 and X 2 Each independently represents -H, -OH, -SH, -NH2, -NHR 11 、-N(R 11 )2. -NHC(O)R 11 、-OR 11 , -C(O)OH, -CHO, or a linear or branched halogenated or unhalogenated alkyl group containing 1 to 12 (e.g., 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12) carbon atoms, wherein X 1 and X 2 At least one of -OH, -SH, -NH2, -NHR 11, -C(O)OH and -CHO, where R 11 represents a straight or branched alkyl group containing 1 to 12 (e.g., 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12) carbon atoms;

[0046] P1, P2, P3, P 1 , P 2 and P 3 each independently represents a polymerizable group;

[0047] Sp1, Sp2, Sp3, Sp 1 、Sp 2 、Sp 3 、Sp 4 、Sp 5 、Sp 7 and Sp 8 each independently represents a spacer group or a single bond;

[0048] Sp 6 Each independently expresses

[0049] X F and X0 each independently represent -O-, -S- or -CO-;

[0050] L F1 and L F2 Each independently represents -H, -F, -Cl, -CF3 or -OCF3;

[0051] Z F1 and Z F2 Each independently represents a single bond, -CO-O-, -O-CO-, -CH2O-, -OCH2-, -CH=CH-, -C≡C-, -CH2CH2-, -CF2CF2-, -(CH2)4-, -CF2O- or -OCF2-;

[0052] Z1, Z2, Z F4 , Z 1 , Z 2 and Z 3 Each independently represents -O-, -S-, -CO-, -CO-O-, -O-CO-, -O-CO-O-, -CH2O-, -OCH2-, -CH2S-, -SCH2-, -CF2O-, -OCF2-, -CF2S-, -SCF2-, -(CH2) d -, -CF2CH2-, -CH2CF2-, -(CF2) d-, -CH=CH-, -CF=CF-, -CH=CF-, -CF=CH-, -C≡C-, -CH=CH-CO-O-, -O-CO-CH=CH-, -CH2CH2-CO-O-, -O-CO-CH2CH2-, -CHR 1 -、-CR 1 R 2 - or a single bond, where R 1 and R 2 Each independently represents a straight or branched alkyl group containing 1 to 12 carbon atoms, and d represents an integer of 1 to 4;

[0053] n F1 and n F2 Each independently represents 0, 1 or 2, where n F1 When it indicates 2, the ring can be the same or different, where n F2 When it indicates 2, the ring Can be the same or different, Z F2 Can be the same or different;

[0054] n F3 represents an integer from 0 to 4 (for example, it can be 1, 2, or 3);

[0055] n F4 represents an integer from 1 to 8 (for example, it can be 2, 3, 4, 5, 6 or 7);

[0056] n s1 Indicates 1, 2, or 3, n s2 represents 1, 2, 3, or 4, and n s1 +n s2 ≥3, where n s1 When it means 2 or 3, can be the same or different, where n s2 When it means 2, 3 or 4, Can be the same or different;

[0057] p s1 、p s2 、p s3 and p s4 Each independently represents 0, 1 or 2, where p s1 When p represents 2, Ls2 can be the same or different. s2 When p represents 2, Ls1 can be the same or different; s3 When it means 2, -Sp 5 -P S3 can be the same or different; when p s4 When 2 is represented, Ls3 may be the same or different; and

[0058] a represents 0, 1 or 2, b represents 0 or 1, wherein when a represents 2, the ring can be the same or different, and Z1 can be the same or different.

[0059] In some embodiments of the present invention, preferably, L F1 and L F2 Each independently represents -F or -Cl.

[0060] As used herein, -CO- and -C(O)- both represent a carbonyl group.

[0061] As used herein, the term "containing 1-r carbon atoms" (wherein r is an integer greater than 1) may mean containing any integer between 1 and r (including the end values ​​1 and r) carbon atoms, for example, containing 2 carbon atoms, containing (r-1) carbon atoms, or containing r carbon atoms. For example, "containing 1-12 carbon atoms" may mean containing 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12 carbon atoms.

[0062] As used herein, the term "integer of y1-y2" can be any integer between the range (including the end values ​​y1 and y2). For example, "integer of 0-12" can be, for example, 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12.

[0063] In some embodiments of the present invention, the compound of formula F is selected from the group consisting of:

[0064]

[0065]

[0066]

[0067]

[0068] as well as

[0069]

[0070] in,

[0071] X F1 and X F2 Each independently represents -CH2- or -O-.

[0072] In some embodiments of the present invention, preferably, n F3 Represents 0.

[0073] In some embodiments of the present invention, preferably, Z F1 and Z F2 Each independently represents a single bond, -CH2O- or -OCH2-; further preferably, Z F1 and Z F2 Both represent single bonds.

[0074] In some embodiments of the present invention, n F1 and n F2 All represent 0.

[0075] In some embodiments of the present invention, in order to obtain an appropriate clearing point, an appropriate optical anisotropy, an appropriate absolute value of dielectric anisotropy, a larger K value, a smaller rotational viscosity, a lower residue concentration, a better pre-tilt angle stability, and a smaller surface roughness of the polymer layer, the liquid crystal composition contains at least two compounds of the general formula F.

[0076] In some embodiments of the present invention, in order to obtain an appropriate clearing point, an appropriate optical anisotropy, an appropriate absolute value of dielectric anisotropy, a larger K value, a smaller rotational viscosity, a lower residue concentration, a better pre-tilt angle stability, and a smaller surface roughness of the polymer layer, the compound of general formula F is selected from the group consisting of compounds of general formula F-1, compounds of general formula F-2, compounds of general formula F-20, compounds of general formula F-21, compounds of general formula F-26, compounds of general formula F-27, compounds of general formula F-30, and compounds of general formula F-31; preferably, the compound of general formula F is selected from the group consisting of compounds of general formula F-1, compounds of general formula F-2, compounds of general formula F-21, compounds of general formula F-27, compounds of general formula F-30, and compounds of general formula F-31.

[0077] In some embodiments of the present invention, preferably, R F1 represents a straight-chain or branched alkyl group containing 1 to 10 carbon atoms, or a straight-chain or branched alkoxy group containing 1 to 9 carbon atoms; further preferably, R F1 It represents a straight chain or branched chain alkyl group having 1 to 8 carbon atoms, or a straight chain or branched chain alkoxy group having 1 to 7 carbon atoms.

[0078] In some embodiments of the present invention, in the compounds of formula F-1, the compounds of formula F-2, the compounds of formula F-3, the compounds of formula F-4, the compounds of formula F-18, the compounds of formula F-19, the compounds of formula F-20, the compounds of formula F-21, the compounds of formula F-22, the compounds of formula F-23, the compounds of formula F-24, the compounds of formula F-25, the compounds of formula F-26, the compounds of formula F-27, the compounds of formula F-28, the compounds of formula F-29, the compounds of formula F-30 and the compounds of formula F-31, R F1 It represents a straight-chain alkoxy group having 1 to 7 carbon atoms.

[0079] The alkenyl group in the present invention is preferably selected from the group represented by any one of formula (V1) to formula (V9), and is particularly preferably a group represented by formula (V1), formula (V2), formula (V8) or (V9). The groups represented by formula (V1) to formula (V9) are as follows:

[0080]

[0081] Wherein, * indicates the connection site in the bonded structure.

[0082] The alkenyloxy group in the present invention is preferably selected from the group represented by any one of formula (OV1) to formula (OV9), and is particularly preferably a group represented by formula (OV1), formula (OV2), formula (OV8) or (OV9). The groups represented by formula (OV1) to formula (OV9) are as follows:

[0083]

[0084] Wherein, * indicates the connection site in the bonded structure.

[0085] In some embodiments of the present invention, it is preferred to adjust the content of the compound of general formula F so that the liquid crystal composition of the present invention has a lower concentration of residues, better pre-tilt angle stability, and smaller surface roughness of the polymer layer while maintaining an appropriate clearing point, an appropriate optical anisotropy, an appropriate absolute value of dielectric anisotropy, a larger K value, and a smaller rotational viscosity.

[0086] In some embodiments of the present invention, the weight percentage of the compound of general formula F in the liquid crystal composition is 0.1%-30% (including any value or sub-range between the range), for example, 0.1%, 0.5%, 1%, 2%, 4%, 6%, 8%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 20%, 22%, 24%, 25%, 26%, 28%, 30%, or a range between any two values ​​therein; preferably 0.1%-25%.

[0087] In some embodiments of the present invention, the polymerizable compound of formula RM is selected from the group consisting of:

[0088]

[0089]

[0090]

[0091]

[0092] as well as

[0093]

[0094] in,

[0095] X1-X 10 and X 12 Each independently represents -F, -Cl, -Sp3-P3, a linear alkyl or alkoxy group containing 1 to 5 carbon atoms,

[0096] In some embodiments of the present invention, X1-X 10 and X 12 Each independently represents -F, -Cl, -Sp3-P3, -CH3, or -OCH3.

[0097] In some embodiments of the present invention, Sp1 and Sp2 both represent single bonds.

[0098] In some embodiments of the present invention, in order to obtain an appropriate clearing point, an appropriate optical anisotropy, an appropriate absolute value of dielectric anisotropy, a larger K value, a smaller rotational viscosity, a lower residue concentration, a better pre-tilt angle stability, and a smaller surface roughness of the polymer layer, the polymerizable compound of the general formula RM is selected from the group consisting of compounds of the general formula RM-1 and compounds of the general formula RM-2.

[0099] The polymerizable groups involved in the present invention are groups suitable for polymerization reactions (e.g., free radical or ionic polymerization, addition polymerization or condensation polymerization), or groups suitable for addition or condensation on the polymer backbone. For chain polymerization, polymerizable groups containing -CH=CH- or -C≡C- are particularly preferred; for ring-opening polymerization, for example, oxetane or epoxy groups are particularly preferred.

[0100] In some embodiments of the present invention, the polymerizable groups P1, P2, P3, P 1 , P 2 and P 3 Each independently expresses or -SH; preferably, the polymerizable groups P1, P2, P3, P 1 , P 2 and P 3 Each independently expresses or -SH; further preferably, the polymerizable groups P1, P2, P3, P 1 , P 2 and P 3 Each independently expresses

[0101] As used herein, the term "spacer group" is known to those skilled in the art and is described in the literature (e.g., Pure Appl. Chem. 2001, 73 (5), 888 and C. Tschierske, G. Pelzl, S. Diele, Angew. Chem. 2004, 116, 6340-6368). As used herein, the term "spacer group" refers to a flexible group that connects the mesogenic group and the polymerizable group in a polymerizable compound. Typical spacer groups are, for example, -(CH2)p1-, -(CH2CH2O)q1-CH2CH2-, -(CH2CH2S)q1-CH2CH2-, -(CH2CH2NH)q1-CH2CH2-, -CR 0 R 00 -(CH2) p1 -or-(SiR 0 R 00 -O)p1-, wherein p1 represents an integer of 1-12 (e.g., 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12), q1 represents an integer of 1-3 (e.g., 1, 2, or 3), and R 0 and R 00Each independently represents -H, a straight or branched alkyl group having 1 to 12 (e.g., 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12) carbon atoms, or a cycloalkyl group having 3 to 12 (e.g., 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12) carbon atoms. Particularly preferred spacer groups are -(CH2)p1-, -(CH2)p1-O-, -(CH2)p1-O-CO-, -(CH2)p1-CO-O-, -(CH2)p1-O-CO-O-, or -CR 0 R 00 -(CH2) p1 -.

[0102] In some embodiments of the present invention, the weight percentage of the polymerizable compound of the general formula RM in the liquid crystal composition is 0.001%-5% (including any numerical value or sub-range between the range), for example, 0.001%, 0.002%, 0.004%, 0.005%, 0.006%, 0.008%, 0.01%, 0.02%, 0.04%, 0.06%, 0.08%, 0.1% , 0.2%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.3%, 0.32%, 0.33%, 0.34%, 0.35%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.6%, 1.8%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or a range between any two of these values.

[0103] In some embodiments of the invention, Ls2 represents -Sp 3 -P 2 ,

[0104] In some embodiments of the invention, Sp 3 、Sp 4 and Sp 5 Each independently represents -(CH2)p1-, -(CH2)p1-O-, -(CH2)p1-O-CO-, -(CH2)p1-CO-O-, -(CH2)p1-O-CO-O- or -CR 0 R 00 -(CH2) p1 -, wherein p1 represents an integer from 1 to 10 (e.g., 2, 3, 4, 5, 6, 7, 8 or 9), R 0 and R 00Each independently represents -H or a linear or branched alkyl group containing 1 to 10 carbon atoms; preferably, in order to obtain a suitable clearing point, a suitable optical anisotropy, a suitable absolute value of dielectric anisotropy, a larger K value, a smaller rotational viscosity, a lower residue concentration, a better pre-tilt angle stability, and a smaller surface roughness of the polymer layer, Sp 3 、Sp 4 and Sp 5 Each independently represents -(CH2)p1- or -(CH2)p1-O-.

[0105] In some embodiments of the present invention, the self-aligning agent of formula SA is selected from the group consisting of the following compounds:

[0106]

[0107]

[0108]

[0109] as well as

[0110]

[0111] in,

[0112] LS 31 Indicates -F, -Cl, -CN, -NO2, -NCO, -NCS, -OCN, -SCN, -C(O)N(R S0 )2. -C(O)R S0 , a straight or branched alkyl group containing 1 to 12 (e.g., 2, 3, 4, 5, 6, 7, 8, 9, 10, or 11) carbon atoms, wherein one or more non-adjacent -CH2- in a straight-chain or branched alkyl group containing 1 to 12 carbon atoms can be independently replaced by -CH=CH-, -C≡C-, -O-, -CO-, -CO-O- or -O-CO-, and wherein a straight-chain or branched alkyl group containing 1 to 12 carbon atoms, One or more -H in the above-mentioned may be independently replaced by -F, wherein R S0 represents a straight or branched alkyl group containing 1 to 12 (e.g., 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12) carbon atoms;

[0113] LS 21 Indicates -Sp 3 -P 2 or and

[0114] Z11 Represents -O-, -S-, -CO-, -CO-O-, -O-CO-, -O-CO-O-, -CH2O-, -OCH2-, -CH2S-, -SCH2-, -CF2O-, -OCF2-, -CF2S-, -SCF2-, -(CH2) d -, -CF2CH2-, -CH2CF2-, -(CF2) d -, -CH=CH-, -CF=CF-, -CH=CF-, -CF=CH-, -C≡C-, -CH=CH-CO-O-, -O-CO-CH=CH-, -CH2CH2-CO-O-, -O-CO-CH2CH2-, -CHR 1 -、-CR 1 R 2 - or a single bond, where R 1 and R 2 Each independently represents a linear or branched alkyl group containing 1 to 12 carbon atoms, and d represents an integer of 1-4.

[0115] In some embodiments of the present invention, the compound of formula SA is selected from the group consisting of a compound of formula SA-1, a compound of formula SA-2, a compound of formula SA-3, and a compound of formula SA-21.

[0116] In some embodiments of the present invention, preferably, Ls1, Ls3 and Ls 31 Each independently represents -F, -Cl, -CN, -NO2, -NCO, -NCS, -OCN, -SCN, -C(O)N(R S0 )2. -C(O)R S0 , a straight chain or branched alkyl group containing 1 to 10 carbon atoms, a straight chain or branched alkoxy group containing 1 to 9 carbon atoms, or a straight chain or branched alkenyl group containing 2 to 10 carbon atoms; further preferably, in order to obtain an appropriate clearing point, an appropriate optical anisotropy, an appropriate absolute value of dielectric anisotropy, a larger K value, a smaller rotational viscosity, a lower residue concentration, a better pre-tilt angle stability, and a smaller surface roughness of the polymer layer, Ls1, Ls3 and Ls 31 Each independently represents -F, -Cl, a straight-chain or branched alkyl group having 1 to 8 carbon atoms, a straight-chain or branched alkoxy group having 1 to 7 carbon atoms, or a straight-chain or branched alkenyl group having 2 to 8 carbon atoms.

[0117] In some embodiments of the present invention, preferably, R S1 Indicates -Sp 1 -P 1, a straight chain or branched chain alkyl group containing 1 to 10 carbon atoms, a straight chain or branched chain alkoxy group containing 1 to 9 carbon atoms, or a straight chain or branched chain alkenyl group containing 2 to 10 carbon atoms; further preferably, R S1 It represents a straight chain or branched chain alkyl group containing 1 to 8 carbon atoms, a straight chain or branched chain alkoxy group containing 1 to 7 carbon atoms, or a straight chain or branched chain alkenyl group containing 2 to 8 carbon atoms.

[0118] In some embodiments of the present invention, R S2 and R S3 Each independently represents -OH, -SH, -NH2, -NHR 11 、-N(R 11 )2. -NHC(O)R 11 、-OR 11 、-C(O)OH、 or -X 1 .

[0119] In some embodiments of the present invention, R S2 and R S3 Each is independently selected from the group consisting of:

[0120]

[0121]

[0122] as well as

[0123] in,

[0124] * indicates the attachment site in the bonded structure.

[0125] In some embodiments of the present invention, in order to obtain an appropriate clearing point, an appropriate optical anisotropy, an appropriate absolute value of dielectric anisotropy, a larger K value, a smaller rotational viscosity, a lower concentration of residues, a better pre-tilt angle stability, and a smaller surface roughness of the polymer layer, R S2 and R S3 Each is independently selected from the group consisting of:

[0126]

[0127]

[0128] as well as Furthermore, R S2 and R S3Each independently preferably is:

[0129] In some embodiments of the present invention, in order to obtain an appropriate clearing point, an appropriate optical anisotropy, an appropriate absolute value of dielectric anisotropy, a larger K value, a smaller rotational viscosity, a lower concentration of residues, a better pre-tilt angle stability, and a smaller surface roughness of the polymer layer, p s1 Indicates 1 or 2.

[0130] In some embodiments of the present invention, the weight percentage of the compound of the general formula SA in the liquid crystal composition is 0.001% to 5% (including any value or sub-range between the range), for example, 0.001%, 0.005%, 0.05%, 0.1%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1.0%, 2%, 3%, 4%, 5%, or a range between any two values ​​therein; preferably, the weight percentage of the compound of the general formula SA in the liquid crystal composition is 0.1% to 2%.

[0131] In the present invention, when the compound of the general formula SA is added to the liquid crystal composition, the liquid crystal composition of the present invention can align the liquid crystal molecules even when a PI alignment layer is not provided.

[0132] In some embodiments of the present invention, the liquid crystal composition further comprises at least one compound of the general formula N:

[0133]

[0134] in,

[0135] R N1 and R N2 each independently represents a straight or branched alkyl group containing 1 to 12 (e.g., 2, 3, 4, 5, 6, 7, 8, 9, 10, or 11) carbon atoms, One or more non-adjacent -CH2- groups in a straight or branched alkyl group containing 1 to 12 carbon atoms may be independently replaced by -CH=CH-, -C≡C-, -O-, -CO-, -CO-O- or -O-CO-;

[0136] ring and ring Each independently expresses in One or more -CH2- in the ring may be replaced by -O-, and one or more single bonds in the ring may be replaced by double bonds, wherein One or more -H in the ring may be replaced by -F, -Cl or -CN, and one or more -CH= in the ring may be replaced by -N=;

[0137] Z N1 and Z N2 Each independently represents a single bond, -CO-O-, -O-CO-, -CH2O-, -OCH2-, -CH=CH-, -C≡C-, -CH2CH2-, -CF2CF2-, -(CH2)4-, -CF2O- or -OCF2-;

[0138] L N1 and L N2 Each independently represents -H, alkyl containing 1-3 (e.g., 1, 2, or 3) carbon atoms, or halogen; and

[0139] n N1 Represents 0, 1, 2, or 3, n N2 Represents 0 or 1, and 0≤n N1 +n N2 ≤3, when n N1 =2 or 3, the ring Can be the same or different, Z N1 Can be the same or different.

[0140] In some embodiments of the present invention, L N1 and L N2 All represent -H.

[0141] In some embodiments of the present invention, the compound of formula N is selected from the group consisting of:

[0142]

[0143]

[0144]

[0145] as well as

[0146]

[0147] In some embodiments of the present invention, preferably, R N1 and R N2 Each independently represents a straight chain or branched alkyl group containing 1 to 10 carbon atoms, a straight chain or branched alkoxy group containing 1 to 9 carbon atoms, or a straight chain or branched alkenyl group containing 2 to 10 carbon atoms; further preferably, R N1 and R N2Each independently represents a straight chain or branched chain alkyl group containing 1 to 8 carbon atoms, a straight chain or branched chain alkoxy group containing 1 to 7 carbon atoms, or a straight chain or branched chain alkenyl group containing 2 to 8 carbon atoms.

[0148] In some embodiments of the present invention, the compound of general formula N is selected from the group consisting of compounds of general formula N-1, compounds of general formula N-2, compounds of general formula N-3, compounds of general formula N-4, compounds of general formula N-9, compounds of general formula N-12, compounds of general formula N-13, compounds of general formula N-19, compounds of general formula N-21, compounds of general formula N-24, compounds of general formula N-27, and compounds of general formula N-30.

[0149] In some embodiments of the present invention, in order to obtain an appropriate clearing point, appropriate optical anisotropy, a larger absolute value of dielectric anisotropy, a larger K value, an appropriate rotational viscosity, a lower residue concentration, better pre-tilt angle stability, and a smaller surface roughness of the polymer layer, the compound of general formula N is selected from the group consisting of compounds of general formula N-2, compounds of general formula N-3, compounds of general formula N-4, compounds of general formula N-9, compounds of general formula N-12, and compounds of general formula N-13.

[0150] In some embodiments of the present invention, in order to obtain an appropriate clearing point, appropriate optical anisotropy, a larger absolute value of dielectric anisotropy, a larger K value, an appropriate rotational viscosity, a lower residue concentration, better pre-tilt angle stability, and a smaller surface roughness of the polymer layer, the compound of general formula N is selected from the group consisting of compounds of general formula N-1, compounds of general formula N-19, compounds of general formula N-21, compounds of general formula N-24, compounds of general formula N-27, and compounds of general formula N-30.

[0151] In some embodiments of the present invention, in order to obtain an appropriate clearing point, appropriate optical anisotropy, a larger absolute value of dielectric anisotropy, a larger K value, an appropriate rotational viscosity, a lower residue concentration, better pre-tilt angle stability, and a smaller surface roughness of the polymer layer, the compound of general formula N is selected from the group consisting of compounds of general formula N-2, compounds of general formula N-9, compounds of general formula N-12, compounds of general formula N-19, and compounds of general formula N-21.

[0152] In some embodiments of the present invention, it is preferred to adjust the content of the compound of the general formula N so that the liquid crystal composition of the present invention has a lower concentration of residues, better pre-tilt angle stability, and smaller surface roughness of the polymer layer while maintaining an appropriate clearing point, an appropriate optical anisotropy, a larger absolute value of dielectric anisotropy, a larger K value, and an appropriate rotational viscosity.

[0153] In some embodiments of the present invention, the weight percentage of the compound of general formula N in the liquid crystal composition is 0.1%-70% (including any numerical value or sub-range between this range), for example, 0.1%, 1%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, 50%, 52%, 54%, 56%, 58%, 60%, 62%, 64%, 66%, 68%, 70%, or the range between any two values.

[0154] In some embodiments of the present invention, the liquid crystal composition further comprises at least one compound of the general formula M:

[0155]

[0156] in,

[0157] R M1 and R M2 each independently represents a straight or branched alkyl group containing 1 to 12 (e.g., 2, 3, 4, 5, 6, 7, 8, 9, 10, or 11) carbon atoms, One or more non-adjacent -CH2- groups in a straight or branched alkyl group containing 1 to 12 carbon atoms may be independently replaced by -CH=CH-, -C≡C-, -O-, -CO-, -CO-O- or -O-CO-;

[0158] ring ring and ring Each independently expresses in One or more -CH2- in the ring may be replaced by -O-, one or more single bonds in the ring may be replaced by double bonds, At most one -H in may be replaced by halogen;

[0159] Z M1 and Z M2 Each independently represents a single bond, -CO-O-, -O-CO-, -CH2O-, -OCH2-, -C≡C-, -CH=CH-, -CH2CH2- or -(CH2)4-; and

[0160] n M represents 0, 1, or 2, where n M =2, ring Can be the same or different, Z M2 Can be the same or different.

[0161] In some embodiments of the present invention, preferably, R M1 and R M2 Each independently represents a straight chain or branched alkyl group containing 1 to 10 carbon atoms, a straight chain or branched alkoxy group containing 1 to 9 carbon atoms, or a straight chain or branched alkenyl group containing 2 to 10 carbon atoms; further preferably, R M1 and R M2 Each independently represents a straight chain or branched chain alkyl group containing 1 to 8 carbon atoms, a straight chain or branched chain alkoxy group containing 1 to 7 carbon atoms, or a straight chain or branched chain alkenyl group containing 2 to 8 carbon atoms.

[0162] In some embodiments of the present invention, R M1 and R M2 Preferably, each independently represents a straight chain alkenyl group containing 2 to 8 carbon atoms; R M1 and R M2 More preferably, each independently represents a straight-chain alkenyl group containing 2 to 5 carbon atoms.

[0163] In some embodiments of the present invention, preferably, R M1 and R M2 One of them is a straight chain alkenyl group having 2 to 5 carbon atoms, and the other is a straight chain alkyl group having 1 to 5 carbon atoms.

[0164] In some embodiments of the present invention, preferably, R M1 and R M2 Each independently represents a straight chain alkoxy group containing 1 to 8 carbon atoms; further preferably, R M1 and R M2 Each independently represents a straight-chain alkoxy group containing 1 to 5 carbon atoms.

[0165] In some embodiments of the present invention, preferably, R M1 and R M2 One of them is a straight-chain alkoxy group having 1 to 5 carbon atoms, and the other is a straight-chain alkyl group having 1 to 5 carbon atoms.

[0166] In some embodiments of the present invention, when reliability is important, R M1 and R M2 are all alkyl groups; when it is important to reduce the volatility of the compound, R M1 and R M2 are all alkoxy groups; when the viscosity reduction is important, R M1 and R M2 At least one of them is alkenyl.

[0167] In some embodiments of the present invention, the compound of formula M is selected from the group consisting of:

[0168]

[0169]

[0170] as well as

[0171]

[0172] In some embodiments of the present invention, in order to obtain an appropriate clearing point, an appropriate optical anisotropy, an appropriate absolute value of dielectric anisotropy, a larger K value, a smaller rotational viscosity, a lower residue concentration, a better pre-tilt angle stability, and a smaller surface roughness of the polymer layer, the compound of general formula M is selected from the group consisting of compounds of general formula M-1, compounds of general formula M-4, compounds of general formula M-11 and compounds of general formula M-13.

[0173] In some embodiments of the present invention, the content of the compound of formula M must be appropriately adjusted according to the required properties such as solubility at low temperature, transition temperature, electrical reliability, birefringence, process adaptability, drip marks, screen burn-in, dielectric anisotropy, etc.

[0174] In some embodiments of the present invention, it is preferred to adjust the content of the compound of the general formula M so that the liquid crystal composition of the present invention has a lower concentration of residues, better pre-tilt angle stability, and smaller surface roughness of the polymer layer while maintaining an appropriate clearing point, an appropriate optical anisotropy, an appropriate absolute value of dielectric anisotropy, a larger K value, and a smaller rotational viscosity.

[0175] In some embodiments of the present invention, the weight percentage of the compound of formula M in the liquid crystal composition is 0.1%-70% (including any value or sub-range between the range), for example, 0.1%, 1%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, 50%, 52%, 54%, 56%, 58%, 60%, 62%, 64%, 66%, 68%, 70%, or the range between any two values.

[0176] In some embodiments of the present invention, the liquid crystal composition of the present invention further comprises at least one compound selected from the group consisting of compounds of formula A-1 and compounds of formula A-2:

[0177]

[0178] in,

[0179] R A1 and R A2 each independently represents a straight or branched alkyl group containing 1 to 12 (e.g., 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12) carbon atoms, One or more non-adjacent -CH2- in a straight-chain or branched alkyl group containing 1 to 12 carbon atoms may be independently replaced by -CH=CH-, -C≡C-, -O-, -CO-, -CO-O- or -O-CO-, and a straight-chain or branched alkyl group containing 1 to 12 carbon atoms, One or more -H in can be independently replaced by -F or -Cl;

[0180] ring ring ring and ring Each independently expresses in One or more -CH2- in the ring may be replaced by -O-, and one or more single bonds in the ring may be replaced by double bonds, wherein One or more -H in the ring may be replaced by -F, -Cl or -CN, and one or more -CH= in the ring may be replaced by -N=;

[0181] Z A11 , Z A21 and Z A22 each independently represents a single bond, -CH2CH2-, -CF2CF2-, -CO-O-, -O-CO-, -O-CO-O-, -CH=CH-, -CF=CF-, -CH2O- or -OCH2-;

[0182] L A11 , L A12 , L A13 , L A21 and L A22 Each independently represents -H, an alkyl group containing 1 to 3 carbon atoms or a halogen;

[0183] X A1 and X A2 Each independently represents halogen, a haloalkyl or haloalkoxy group containing 1 to 5 carbon atoms, a haloalkenyl or haloalkenyloxy group containing 2 to 5 carbon atoms;

[0184] n A11 represents 0, 1, 2, or 3, where n A11 =2 or 3, the ring Can be the same or different, Z A11 Can be the same or different;

[0185] n A12 represents 1 or 2, where n A12 =2, ring may be the same or different; and

[0186] n A2 represents 0, 1, 2, or 3, where n A2 =2 or 3, the ring Can be the same or different, Z A21 Can be the same or different.

[0187] In some embodiments of the present invention, the weight percentage of the compound selected from the group consisting of the compound of the general formula A-1 and the compound of the general formula A-2 in the liquid crystal composition is 0.1%-60% (including any value between the range), for example, 0.1%, 1%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, 50%, 52%, 54%, 56%, 58%, 60%, or a range between any two of the values.

[0188] In some embodiments of the present invention, the compound of formula A-1 is selected from the group consisting of the following compounds:

[0189]

[0190]

[0191]

[0192] as well as

[0193]

[0194] in,

[0195] R A1 represents a straight or branched alkyl group containing 1 to 8 carbon atoms, One or more non-adjacent -CH2- in a straight or branched alkyl group containing 1 to 8 carbon atoms may be independently replaced by -CH=CH-, -C≡C-, -O-, -CO-, -CO-O- or -O-CO-, and one or more -H present in these groups may be independently replaced by -F or -Cl;

[0196] R vand R w Each independently represents -CH2- or -O-;

[0197] L A11 , L A12 , L A11 ', L A12 ', L A14 , L A15 and L A16 Each independently represents -H or -F;

[0198] L A13 and L A13 'Each independently represents -H or -CH3;

[0199] X A1 represents -F, -CF3 or -OCF3; and

[0200] v and w each independently represent 0 or 1.

[0201] In some embodiments of the present invention, the weight percentage of the compound of general formula A-1 in the liquid crystal composition is 0.1%-50% (including any value or sub-range between the range), for example, 0.1%, 1%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, 50%, or a range between any two values.

[0202] Regarding the preferred content of the compound of general formula A-1, when the viscosity of the liquid crystal composition of the present invention is kept low and the response speed is fast, it is preferred to make its lower limit value slightly lower and its upper limit value slightly lower; further, when the clearing point of the liquid crystal composition of the present invention is kept high and the temperature stability is good, it is preferred to make its lower limit value slightly lower and its upper limit value slightly lower; in addition, in order to keep the driving voltage low and increase the absolute value of dielectric anisotropy, it is preferred to make its lower limit value slightly higher and its upper limit value slightly higher.

[0203] In some embodiments of the present invention, the compound of formula A-2 is selected from the group consisting of:

[0204]

[0205]

[0206] as well as

[0207]

[0208] in,

[0209] R A2 represents a straight-chain or branched alkyl group containing 1 to 8 carbon atoms, one or more non-adjacent -CH2- groups in the straight-chain or branched alkyl group containing 1 to 8 carbon atoms may be independently replaced by -CH=CH-, -C≡C-, -O-, -CO-, -CO-O- or -O-CO-, and one or more -H groups in these groups may be independently replaced by -F or -Cl;

[0210] L A21 , L A22 , L A23 , L A24 and L A25 each independently represents -H or -F; and

[0211] X A2 It represents -F, -CF3, -OCF3 or -CH2CH2CH=CF2.

[0212] In some embodiments of the present invention, the weight percentage of the compound of general formula A-2 in the liquid crystal composition is 0.1%-50% (including any values ​​between the range), for example, 0.1%, 1%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, 50%, or a range between any two of the values.

[0213] Regarding the preferred content of the compound of general formula A-2, when the viscosity of the liquid crystal composition of the present invention is kept low and the response speed is fast, it is preferred to make its lower limit value slightly lower and its upper limit value slightly lower; further, when the clearing point of the liquid crystal composition of the present invention is kept high and the temperature stability is good, it is preferred to make its lower limit value slightly lower and its upper limit value slightly lower; in addition, in order to keep the driving voltage low and increase the absolute value of the dielectric anisotropy, it is preferred to make its lower limit value slightly higher and its upper limit value slightly higher.

[0214] In some embodiments of the present invention, the liquid crystal composition further comprises at least one compound of formula B

[0215]

[0216] in,

[0217] R B1 and R B2Each independently represents halogen, -CF3, -OCF3, a linear or branched alkyl group containing 1 to 12 (e.g., 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12) carbon atoms, A straight or branched alkyl group containing 1 to 12 carbon atoms, One or more non-adjacent -CH2- can be independently replaced by -CH=CH-, -C≡C-, -CO-, -CO-O- or -O-CO-;

[0218] ring and ring Each independently expresses in One or more -CH2- in the ring may be replaced by -O-, and one or more single bonds in the ring may be replaced by double bonds, wherein One or more -H in the ring may be independently replaced by -CN, -F or -Cl, and one or more -CH= in the ring may be replaced by -N=;

[0219] X B represents -O-, -S-, or -CO-;

[0220] L B1 and L B2 Each independently represents -H, -F, -Cl, -CF3 or -OCF3;

[0221] Z B1 and Z B2 Each independently represents a single bond, -O-, -S-, -CO-O-, -O-CO-, -CH2O-, -OCH2-, -CH=CH-, -C≡C-, -CH2CH2-, -CF2CF2-, -(CH2)4-, -CF2O- or -OCF2-; and

[0222] n B1 and n B2 Each independently represents 0, 1 or 2, where n B1 When it indicates 2, the ring can be the same or different, where n B2 When it indicates 2, the ring Can be the same or different.

[0223] In some embodiments of the present invention, the compound of formula B is selected from the group consisting of:

[0224]

[0225]

[0226] as well as

[0227]

[0228] Among them, R B1 ' and R B2 ' Each independently represents a straight chain alkyl group containing 1 to 8 carbon atoms.

[0229] In some embodiments of the present invention, the weight percentage of the compound of general formula B in the liquid crystal composition is 0.1%-30% (including any value or sub-range between the range), for example, 0.1%, 1%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, or a range between any two values.

[0230] In some embodiments of the present invention, the liquid crystal composition further comprises at least one additive.

[0231] In addition to the above compounds, the liquid crystal composition of the present invention may also contain conventional nematic liquid crystals, smectic liquid crystals, cholesteric liquid crystals, dopants, antioxidants, ultraviolet absorbers, infrared absorbers, polymerizable monomers or light stabilizers.

[0232] Possible dopants which are preferably added to the liquid crystal composition according to the invention are shown below:

[0233]

[0234]

[0235] as well as

[0236]

[0237] In some embodiments of the present invention, the weight percentage of the dopant in the liquid crystal composition is 0%-5%; preferably, the weight percentage of the dopant in the liquid crystal composition is 0.01%-1%.

[0238] In addition, the antioxidant, light stabilizer, ultraviolet absorber and other additives used in the liquid crystal composition of the present invention are preferably the following:

[0239]

[0240]

[0241]

[0242]

[0243] Here, n represents a positive integer from 1 to 12.

[0244] Preferably, the antioxidant is selected from the compounds shown below:

[0245]

[0246] In some embodiments of the present invention, the additive accounts for 0%-5% of the total weight of the liquid crystal composition; preferably, the additive accounts for 0.01%-1% of the total weight of the liquid crystal composition.

[0247] Even in the absence of a polymerization initiator, the liquid crystal composition containing a polymerizable compound of the present invention can be polymerized, but in order to promote polymerization, a polymerization initiator may be further contained therein. Examples of the polymerization initiator include benzoin ethers, benzophenones, acetophenones, benzyl ketals, acylphosphine oxides, and the like.

[0248] For the polymerization method of the polymerizable compound, since it is expected that the polymerization proceeds quickly, a method of polymerization by irradiation with active energy lines such as ultraviolet rays or electron beams is preferred. When using ultraviolet rays, a polarized light source can be used, or a non-polarized light source can be used. In addition, when the liquid crystal composition is polymerized in a state where it is clamped between two substrates, at least the substrate on the irradiated side must have appropriate transparency relative to the active energy line. In addition, a mask can be used during light irradiation to polymerize only a specific part, and then, by changing conditions such as the electric field, magnetic field or temperature, the orientation state of the unpolymerized part is changed, and further irradiation with active energy lines is performed for polymerization. In particular, when ultraviolet exposure is performed, it is preferred to perform ultraviolet exposure while applying a voltage to the liquid crystal composition.

[0249] The temperature during irradiation with active energy rays such as ultraviolet rays or electron beams is preferably within a temperature range that maintains the liquid crystal state of the liquid crystal composition of the present invention. Polymerization is preferably performed at a temperature close to room temperature (i.e., 15-35°C). As for the lamp that generates ultraviolet rays, metal halide lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, etc. can be used. In addition, as for the wavelength of the irradiated ultraviolet rays, it is preferred to irradiate ultraviolet rays with a wavelength outside the absorption wavelength region of the liquid crystal composition, and it is preferred to use ultraviolet rays that are blocked as needed. The intensity of the irradiated ultraviolet rays is preferably 0.1mW / cm 2 -50 mW / cm 2 When irradiating ultraviolet rays, the intensity can be changed, and the time of irradiating ultraviolet rays can be appropriately selected according to the intensity of the irradiated ultraviolet rays, preferably 10s-600s.

[0250] In another aspect, the present invention further provides a liquid crystal display device, comprising the liquid crystal composition.

[0251] In some embodiments of the present invention, the liquid crystal composition is particularly suitable for use in PSA-VA, PSA-OCB, PSA-IPS, PSA-FFS and PSA-TN type liquid crystal display devices.

[0252] As used herein, the terms "tilt" and "tilt angle" are to be understood as the tilted alignment of the liquid crystal molecules relative to the surface of the liquid crystal cell in a liquid crystal display device (preferably, a PSA type liquid crystal display device). The tilt angle represents the average angle (<90°) formed between the longitudinal molecular axes (liquid crystal director) of the liquid crystal molecules and the surface of the outer plate of the liquid crystal cell. A low value of the tilt angle (i.e., a large angle deviating from 90°) corresponds to a large tilt.

[0253] Beneficial effects: Compared with the prior art, the liquid crystal composition of the present invention has an appropriate clearing point, an appropriate optical anisotropy, an appropriate absolute value of dielectric anisotropy, a larger K value, a smaller rotational viscosity, a smaller residue concentration, a better pre-tilt angle stability, and a smaller polymer layer surface roughness, so that the liquid crystal display device containing the liquid crystal composition has a higher contrast, a faster response speed, and can achieve vertical alignment of liquid crystal molecules without a PI alignment layer while maintaining an appropriate temperature use range and an appropriate threshold voltage. It can effectively accelerate the production process of PSA-type liquid crystal displays, increase production efficiency, and can effectively improve the problems existing in existing PSA-type liquid crystal displays such as "image viscosity", uneven display, "broken bright spots", etc., and has a high practical application value. DETAILED DESCRIPTION

[0254] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.

[0255] Unless otherwise specified in the present invention, all ratios are weight ratios and all temperatures are degrees Celsius.

[0256] For ease of expression, in the following examples, the group structure of each compound is represented by the code listed in Table 1:

[0257] Table 1 Group structure codes of compounds

[0258]

[0259]

[0260] Take the following compound as an example:

[0261]

[0262] If the structural formula is represented by the codes listed in Table 1, it can be expressed as: nCCGF, where n in the code represents the number of C atoms in the left-end alkyl group, for example, n is "3", which means that the alkyl group is -C3H7; C in the code represents 1,4-cyclohexylene, G represents 2-fluoro-1,4-phenylene, and F represents a fluorine substituent.

[0263] The abbreviated codes for the test items in the following embodiments are as follows:

[0264] Cp clearing point (nematic-isotropic phase transition temperature, °C)

[0265] Δn optical anisotropy (589nm, 20℃)

[0266] Δε Dielectric anisotropy (1KHz, 20℃)

[0267] K 11 Splay elastic constant (20℃)

[0268] K 33 Bending elastic constant (20℃)

[0269] γ1 Rotational viscosity (mPa·s, 20℃)

[0270] Ra Surface roughness (nm)

[0271] PTA pre-tilt angle (°, 20°C)

[0272] ΔPTA Pre-tilt angle stability (change in pre-tilt angle after applying voltage for a fixed time, °)

[0273] in,

[0274] Cp: ​​obtained by melting point test.

[0275] Δn: measured using an Abbe refractometer under a sodium lamp (589 nm) at 20°C.

[0276] Δε:Δε=ε ‖ -ε ⊥ , where ε ‖ is the dielectric constant parallel to the molecular axis, ε ⊥ is the dielectric constant perpendicular to the molecular axis; test conditions: 20°C, 1KHz, VA type test box with a box thickness of 6μm.

[0277] γ1: obtained by testing using LCM-2 liquid crystal property evaluation system; test conditions: 20°C, 160-260V, test box thickness 20μm.

[0278] K11 and K 33 : The CV curve of the liquid crystal is tested and calculated using an LCR meter and a VA test box; test conditions: box thickness 6μm, V=0.1~20V, 20℃.

[0279] Ra: After a liquid crystal composition containing a polymerizable compound is polymerized by UV light, the liquid crystal molecules are washed away, and then an atomic force microscope (AFM) is used to measure the surface roughness of the polymer layer after polymerization.

[0280] PTA: Using the crystal rotation method, the liquid crystal was poured into a VA test box (box thickness 3.5 μm), a voltage (15 V, 60 Hz) was applied, and UV light UV1 (5.5 mw / cm -2 , 313nm) to irradiate the polymerizable compound to form a pre-tilt angle PTA1, and then continue to irradiate the liquid crystal composition having formed a pre-tilt angle PTA1 with ultraviolet light UV2 (0.25mw / cm -2 , 313nm) to eliminate the residual polymerizable compound in the PTA1 state, and the pre-tilt angle formed by the polymerizable compound at this time is PTA2. The present invention examines the polymerization speed of the polymerizable compound by comparing the size of the pre-tilt angle formed when UV1 is irradiated for the same time (the smaller the pre-tilt angle, the faster the polymerization speed) or comparing the time required to form the same pre-tilt angle (the shorter the time required, the faster the polymerization speed).

[0281] ΔPTA: After the test box used in the pre-tilt angle PTA test has a pre-tilt angle of 88±0.2° through UV1 and UV2 steps, a 60Hz SW wave, a 20V AC voltage and a 2V DC voltage are applied to the test box. After a fixed period of time at 40°C and in the presence of backlight, the pre-tilt angle of the test box is tested. ΔPTA(168h)=PTA(initial)-PTA(168h). The smaller ΔPTA(168h) is, the better the stability of the pre-tilt angle is.

[0282] Residue concentration: After applying UV2 irradiation for 90 min, the liquid crystal eluted from the liquid crystal test box was detected by high performance liquid chromatography (HPLC), and the concentration of the polymerizable compound and the self-aligning agent therein was referred to as the residue concentration.

[0283] Each component used in the following examples can be synthesized by a known method or obtained through commercial channels. These synthesis techniques are conventional, and each liquid crystal compound obtained meets the standards of electronic compounds after testing.

[0284] Liquid crystal compositions are prepared according to the ratios of the liquid crystal compositions specified in the following examples. The preparation of the liquid crystal compositions is carried out according to conventional methods in the art, such as mixing in proportion by heating, ultrasonic waves, suspension, etc.

[0285] The structures of the polymerizable compounds used in the following examples are shown in Table 2 below.

[0286] Table 2 Polymerizable compounds used in the examples

[0287]

[0288] The structures of the self-aligning agents used in the following examples are shown in Table 3 below.

[0289] Table 3 Self-aligning agents used in the examples

[0290]

[0291]

[0292] Comparative Examples 1-2 and Examples 1-3

[0293] The main liquid crystal compositions of control Host-1, control Host-2, Host-1, Host-2 and Host-3 were prepared according to the compounds listed in Table 4 and their weight percentages, and filled between two substrates of a liquid crystal display for performance testing.

[0294] Table 4 Formulation of host liquid crystal composition and performance parameter test results

[0295]

[0296] 0.3 parts by weight of polymerizable compound RM-01 and 0.6 parts by weight of Add-1 were added to 100 parts by weight of the main liquid crystal composition control Host-1 and control Host-2 to prepare the liquid crystal compositions of Comparative Examples 1 and 2, respectively, and 0.3 parts by weight of polymerizable compound RM-01 and 0.6 parts by weight of Add-1 were added to 100 parts by weight of the main liquid crystal composition Host-1, Host-2 and Host-3 to prepare the liquid crystal compositions of Examples 1-3, respectively. The physical property values ​​of each liquid crystal composition obtained were almost unchanged relative to the respective main liquid crystal compositions. The obtained liquid crystal compositions were filled into "non-aligned" test boxes (the box thickness d was 3.5 μm, with ITO coatings on both sides (structured ITO in the case of multi-domain switching), no alignment layer, and no passivation layer) for performance testing. The relevant performance test results of the liquid crystal compositions of Comparative Examples 1-2 and Examples 1-3 are shown in Table 5 below.

[0297] Table 5 Performance test results of the liquid crystal compositions of Comparative Examples 1-2 and Examples 1-3

[0298]

[0299] From the comparison between Examples 1-3 and Comparative Examples 1-2, it can be seen that the combination of the compound of the general formula F, the polymerizable compound of the general formula RM and the self-aligning agent of the general formula SA enables the liquid crystal composition of the present application to maintain an appropriate clearing point, an appropriate optical anisotropy, an appropriate absolute value of dielectric anisotropy, a larger K value (K 11 and K 33 ) and smaller rotational viscosity, the concentration of the residue after 90 min of UV2 irradiation is lower, the pre-tilt angle stability is better after voltage treatment under the same conditions, and the surface roughness of the polymer layer is smaller.

[0300] Comparative Examples 3-4 and Examples 4-6

[0301] 0.3 parts by weight of polymerizable compound RM-01 and 0.6 parts by weight of Add-2 were added to 100 parts by weight of the main liquid crystal composition control Host-1 and control Host-2 to prepare the liquid crystal compositions of Comparative Examples 3 and 4, respectively, and 0.3 parts by weight of polymerizable compound RM-01 and 0.6 parts by weight of Add-2 were added to 100 parts by weight of the main liquid crystal composition Host-1, Host-2 and Host-3 to prepare the liquid crystal compositions of Examples 4-6, respectively. The physical property values ​​of each liquid crystal composition obtained were almost unchanged relative to the respective main liquid crystal compositions. The obtained liquid crystal compositions were filled into "non-aligned" test boxes (the box thickness d was 3.5 μm, with ITO coatings on both sides (structured ITO in the case of multi-domain switching), no alignment layer, and no passivation layer) for performance testing. The relevant performance test results of the liquid crystal compositions of Comparative Examples 3-4 and Examples 4-6 are shown in Table 6 below.

[0302] Table 6 Performance test results of liquid crystal compositions of comparative examples 3-4 and examples 4-6

[0303]

[0304] From the comparison between Examples 4-6 and Comparative Examples 3-4, it can be seen that the combination of the compound of the general formula F, the polymerizable compound of the general formula RM and the self-aligning agent of the general formula SA enables the liquid crystal composition of the present application to maintain an appropriate clearing point, an appropriate optical anisotropy, an appropriate absolute value of dielectric anisotropy, a larger K value (K 11 and K 33) and smaller rotational viscosity, the concentration of the residue after 90 min of UV2 irradiation is lower, the pre-tilt angle stability is better after voltage treatment under the same conditions, and the surface roughness of the polymer layer is smaller.

[0305] Comparative Examples 5-6 and Examples 7-9

[0306] 0.3 parts by weight of polymerizable compound RM-02 and 0.6 parts by weight of Add-3 were added to 100 parts by weight of the main liquid crystal composition control Host-1 and control Host-2 to prepare the liquid crystal compositions of Comparative Examples 5 and 6, respectively, and 0.3 parts by weight of polymerizable compound RM-02 and 0.6 parts by weight of Add-3 were added to 100 parts by weight of the main liquid crystal composition Host-1, Host-2 and Host-3 to prepare the liquid crystal compositions of Examples 7-9, respectively. The physical property values ​​of each liquid crystal composition obtained are almost unchanged relative to the respective main liquid crystal compositions. The obtained liquid crystal compositions were filled into "non-aligned" test boxes (the box thickness d was 3.5 μm, with ITO coatings on both sides (structured ITO in the case of multi-domain switching), no alignment layer, and no passivation layer) for testing. The performance test results of the liquid crystal compositions of Comparative Examples 5-6 and Examples 7-9 are shown in Table 7 below.

[0307] Table 7 Performance test results of liquid crystal compositions of Comparative Examples 5-6 and Examples 7-9

[0308]

[0309] From the comparison between Examples 7-8 and Comparative Examples 5-6, it can be seen that the combination of the compound of the general formula F, the polymerizable compound of the general formula RM and the self-aligning agent of the general formula SA enables the liquid crystal composition of the present application to maintain an appropriate clearing point, an appropriate optical anisotropy, an appropriate absolute value of dielectric anisotropy, a larger K value (K 11 and K 33 ) and smaller rotational viscosity, the concentration of the residue after 90 min of UV2 irradiation is lower, the pre-tilt angle stability is better after voltage treatment under the same conditions, and the surface roughness of the polymer layer is smaller.

[0310] Comparative Examples 7-8 and Examples 10-12

[0311] 0.3 parts by weight of polymerizable compound RM-02 and 0.6 parts by weight of Add-5 were added to 100 parts by weight of the main liquid crystal composition control Host-1 and control Host-2 to prepare the liquid crystal compositions of Comparative Examples 7 and 8, respectively, and 0.3 parts by weight of polymerizable compound RM-02 and 0.6 parts by weight of Add-5 were added to 100 parts by weight of the main liquid crystal composition Host-1, Host-2 and Host-3 to prepare the liquid crystal compositions of Examples 10-12, respectively. The physical property values ​​of each liquid crystal composition obtained were almost unchanged relative to the respective main liquid crystal compositions. The obtained liquid crystal compositions were filled into "non-aligned" test boxes (the box thickness d was 3.5 μm, with ITO coatings on both sides (structured ITO in the case of multi-domain switching), no alignment layer, and no passivation layer) for performance testing. The relevant performance test results of the liquid crystal compositions of Comparative Examples 7-8 and Examples 10-12 are shown in Table 8 below.

[0312] Table 8 Performance test results of the liquid crystal compositions of Comparative Examples 7-8 and Examples 10-12

[0313]

[0314] From the comparison between Examples 10-12 and Comparative Examples 7-8, it can be seen that the combination of the compound of the general formula F, the polymerizable compound of the general formula RM and the self-aligning agent of the general formula SA enables the liquid crystal composition of the present application to maintain an appropriate clearing point, an appropriate optical anisotropy, an appropriate absolute value of dielectric anisotropy, a larger K value (K 11 and K 33 ) and smaller rotational viscosity, it is even lower after 90 min of UV2 irradiation, and has better pre-tilt angle stability and smaller surface roughness of the polymer layer after voltage treatment under the same conditions.

[0315] Comparative Examples 9-11 and Examples 13-14

[0316] The main liquid crystal compositions of control Host-3, control Host-4, control Host-5, Host-4 and Host-5 were prepared according to the compounds listed in Table 9 and their weight percentages, and filled between the two substrates of the liquid crystal display for performance testing.

[0317] Table 9 Formulation and performance parameter test results of the main liquid crystal composition

[0318]

[0319] 0.3 parts by weight of polymerizable compound RM-01 and 0.4 parts by weight of Add-4 were added to 100 parts by weight of the main liquid crystal composition control Host-3, control Host-4 and control Host-5 to prepare the liquid crystal compositions of comparative examples 9-11, respectively, and 0.3 parts by weight of polymerizable compound RM-01 and 0.4 parts by weight of Add-4 were added to 100 parts by weight of the main liquid crystal composition Host-4 and Host-5 to prepare the liquid crystal compositions of embodiments 13-14, respectively. The physical property values ​​of each liquid crystal composition obtained were almost unchanged relative to the respective main liquid crystal compositions. The obtained liquid crystal compositions were respectively filled into "non-aligned" test boxes (the box thickness d was 3.5 μm, with ITO coating on both sides (structured ITO in the case of multi-domain switching), no alignment layer, and no passivation layer) for performance testing. The performance test results of the liquid crystal compositions of comparative examples 9-11 and embodiments 13-14 are shown in Table 10 below.

[0320] Table 10 Performance test results of the liquid crystal compositions of Comparative Examples 9-11 and Examples 13-14

[0321]

[0322] From the comparison between Examples 13-14 and Comparative Examples 9-11, it can be seen that the combination of the compound of the general formula F, the polymerizable compound of the general formula RM and the self-aligning agent of the general formula SA enables the liquid crystal composition of the present application to maintain an appropriate clearing point, an appropriate optical anisotropy, an appropriate absolute value of dielectric anisotropy, a larger K value (K 11 and K 33 ) and smaller rotational viscosity, the concentration of the residue after 90 min of UV2 irradiation is lower, and it has better pre-tilt angle stability and smaller surface roughness of the polymer layer after voltage treatment under the same conditions.

[0323] Comparative Examples 12-13 and Examples 15-16

[0324] The main liquid crystal compositions of control Host-6, control Host-7, Host-6 and Host-7 were prepared according to the compounds listed in Table 11 and their weight percentages, and filled between two substrates of a liquid crystal display for performance testing.

[0325] Table 11 Formulation and performance parameter test results of the main liquid crystal composition

[0326]

[0327] 0.3 parts by weight of polymerizable compound RM-02 and 0.6 parts by weight of Add-6 were added to 100 parts by weight of the main liquid crystal composition control Host-6 and control Host-7 to prepare the liquid crystal compositions of comparative examples 12-13, respectively, and 0.3 parts by weight of polymerizable compound RM-02 and 0.6 parts by weight of Add-6 were added to 100 parts by weight of the main liquid crystal composition Host-6 and Host-7 to prepare the liquid crystal compositions of embodiments 15-16, respectively. The physical property values ​​of each liquid crystal composition obtained were almost unchanged relative to the respective main liquid crystal compositions. The obtained liquid crystal compositions were respectively filled into "non-aligned" test boxes (the box thickness d was 3.5 μm, with ITO coatings on both sides (structured ITO in the case of multi-domain switching), no alignment layer and no passivation layer) for performance testing. The performance test results of the liquid crystal compositions of comparative examples 12-13 and embodiments 15-16 are shown in Table 12 below.

[0328] Table 12 Performance test results of the liquid crystal compositions of Comparative Examples 12-13 and Examples 15-16

[0329]

[0330] From the comparison between Examples 15-16 and Comparative Examples 12-13, it can be seen that the combination of the compound of the general formula F, the polymerizable compound of the general formula RM and the self-aligning agent of the general formula SA enables the liquid crystal composition of the present application to maintain an appropriate clearing point, an appropriate optical anisotropy, an appropriate absolute value of dielectric anisotropy, a larger K value (K 11 and K 33 ) and smaller rotational viscosity, the concentration of the residue after applying UV2 for 90 min is lower, and it has better pre-tilt angle stability and smaller surface roughness of the polymer layer after voltage treatment under the same conditions.

[0331] In summary, the liquid crystal composition of the present invention has a low concentration of residues after 90 minutes of UV2 irradiation, good pre-tilt angle stability (i.e., good stability) after voltage treatment under the same conditions, and a small surface roughness of the polymer layer, while maintaining an appropriate clearing point, an appropriate optical anisotropy, an appropriate absolute value of dielectric anisotropy, a large K value, and a small rotational viscosity. This allows a liquid crystal display device containing the liquid crystal composition to have a high contrast ratio and a fast response speed while maintaining an appropriate temperature use range and an appropriate threshold voltage. It can achieve vertical alignment of liquid crystal molecules without a PI alignment layer, can effectively accelerate the production process of PSA-type liquid crystal displays, improve production efficiency, and can effectively improve problems such as "image viscosity", uneven display, "broken bright spots", etc. in existing PSA-type liquid crystal displays, and has a high practical application value.

[0332] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A liquid crystal composition, characterized in that: The liquid crystal composition comprises: At least one compound of formula F, wherein the compound of formula F is selected from the group consisting of: and At least one polymerizable compound of the general formula RM At least one self-aligning agent of the general formula SA At least one compound of the general formula N as well as At least one compound of the general formula M in, R F1 represents -H, halogen, a straight or branched alkyl group containing 1 to 12 carbon atoms, One or more non-adjacent -CH2- in the straight-chain or branched alkyl group containing 1 to 12 carbon atoms may be independently replaced by -C≡C-, -O-, -CO-, -CO-O- or -O-CO-, and one or more -H in the straight-chain or branched alkyl group containing 1 to 12 carbon atoms may be independently replaced by -F or -Cl; R F3 represents a straight or branched chain alkyl group containing 1 to 4 carbon atoms; R1 represents -H, halogen, -CN, -Sp2-P2, a straight or branched alkyl group containing 1 to 12 carbon atoms, wherein the straight or branched alkyl group containing 1 to 12 carbon atoms, One or more non-adjacent -CH2- may be independently replaced by -CH=CH-, -C≡C-, -O-, -CO-, -CO-O- or -O-CO-, and one or more -H may be independently replaced by -F or -Cl; R S1 Indicates -Sp 1 -P 1 , a straight or branched alkyl group containing 1 to 12 carbon atoms, wherein one or more non-adjacent -CH2- in the straight-chain or branched alkyl group containing 1 to 12 carbon atoms can be independently replaced by -CH=CH-, -C≡C-, -O-, -CO-, -CO-O- or -O-CO-, and the straight-chain or branched alkyl group containing 1 to 12 carbon atoms, One or more -H in can be independently replaced by -F or -Cl; ring and ring Each independently expresses in One or more -CH2- in the ring may be replaced by -O-, and one or more single bonds in the ring may be replaced by double bonds, wherein One or more -H in the group may be replaced independently by -F, -Cl, -CN, -Sp3-P3, a halogenated or unhalogenated straight-chain alkyl group containing 1 to 12 carbon atoms, a halogenated or unhalogenated straight-chain alkoxy group containing 1 to 11 carbon atoms, substituted, and -CH= in one or more rings may be replaced by -N=; ring express in One or more -H in the group may be replaced independently by -F, -Cl, -CN, -Sp3-P3, a halogenated or unhalogenated straight-chain alkyl group containing 1 to 12 carbon atoms, a halogenated or unhalogenated straight-chain alkoxy group containing 1 to 11 carbon atoms, substituted, and -CH= in one or more rings may be replaced by -N=; ring express in One or more -CH2- in the ring may be replaced by -O-, and one or more single bonds in the ring may be replaced by double bonds; Ls1 and Ls3 each independently represent -F, -Cl, -CN, -NO2, -NCO, -NCS, -OCN, -SCN, -C(O)N(R S0 )2. -C(O)R S0 , a straight or branched alkyl group containing 1 to 12 carbon atoms, wherein one or more non-adjacent -CH2- in the straight-chain or branched alkyl group containing 1 to 12 carbon atoms can be independently replaced by -CH=CH-, -C≡C-, -O-, -CO-, -CO-O- or -O-CO-, and the straight-chain or branched alkyl group containing 1 to 12 carbon atoms, One or more -H in the above-mentioned may be independently replaced by -F, wherein R S0 represents a straight or branched chain alkyl group containing 1 to 12 carbon atoms; Ls2 means -Sp 3 -P 2 or R S2 and R S3 Each independently represents an anchoring group, the anchoring group is Where * indicates the connection site in the bonded structure; p represents 1 or 2, wherein when p represents 2, -Sp 8 -X 2 Can be the same or different; o means 0 or 1; M S1 express I S1 and J S1 Each independently represents -CH2-, -O- or -S-; N S1 Indicates =O or =S; V K1 、V K2 and V K3 Each independently represents -CH= or -N=; X 1 and X 2 Each independently represents -H, -OH, -SH, -NH2, -NHR 11 、-N(R 11 )2. -NHC(O)R 11 、-OR 11 , -C(O)OH, -CHO, or a linear or branched halogenated or unhalogenated alkyl group containing 1 to 12 carbon atoms, wherein X 1 and X 2 At least one of -OH, -SH, -NH2, -NHR 11 , -C(O)OH and -CHO, where R 11 represents a straight or branched chain alkyl group containing 1 to 12 carbon atoms; P1, P2, P3, P 1 , P 2 and P 3 each independently represents a polymerizable group; Sp1, Sp2, Sp3, Sp 1 、Sp 2 、Sp 3 、Sp 4 、Sp 5 、Sp 7 and Sp 8 each independently represents a spacer group or a single bond; Sp 6 Each independently expresses X F1 and X F2 Each independently represents -CH2- or -O-; X0 represents -O-, -S- or -CO-; Z F1 represents a single bond, -CO-O-, -O-CO-, -CH2O-, -OCH2-, -CH=CH-, -C≡C-, -CH2CH2-, -CF2CF2-, -(CH2)4-, -CF2O- or -OCF2-; Z1, Z2, Z 1 and Z 2 Each independently represents -O-, -S-, -CO-, -CO-O-, -O-CO-, -O-CO-O-, -CH2O-, -OCH2-, -CH2S-, -SCH2-, -CF2O-, -OCF2-, -CF2S-, -SCF2-, -(CH2) d -, -CF2CH2-, -CH2CF2-, -(CF2) d -, -CH=CH-, -CF=CF-, -CH=CF-, -CF=CH-, -C≡C-, -CH=CH-CO-O-, -O-CO-CH=CH-, -CH2CH2-CO-O-, -O-CO-CH2CH2-, -CHR 1 -、-CR 1 R 2 - or a single bond, where R 1 and R 2 Each independently represents a straight or branched alkyl group containing 1 to 12 carbon atoms, and d represents an integer of 1 to 4; n F4 Indicates an integer from 1 to 8; n s1 Indicates 1, 2, or 3, n s2 represents 1, 2, 3, or 4, and n s1 +n s2 ≥3, where n s1 When it means 2 or 3, can be the same or different, where n s2 When it means 2, 3 or 4, Can be the same or different; p s1 、p s2 、p s3 and p s4 Each independently represents 0, 1 or 2, where p s1 When p represents 2, Ls2 can be the same or different. s2 When p represents 2, Ls1 can be the same or different; s3 When it means 2, -Sp 5 -R S3 can be the same or different; when p s4 When it represents 2, Ls3 can be the same or different; a represents 0, 1 or 2, b represents 0 or 1, wherein when a represents 2, the ring can be the same or different, Z1 can be the same or different; R N1 and R N2 Each independently represents a straight or branched alkyl group containing 1 to 12 carbon atoms, One or more non-adjacent -CH2- in the linear or branched alkyl group containing 1 to 12 carbon atoms may be independently replaced by -CH=CH-, -C≡C-, -O-, -CO-, -CO-O- or -O-CO-; ring and ring Each independently expresses in One or more -CH2- in the ring may be replaced by -O-, and one or more single bonds in the ring may be replaced by double bonds, wherein One or more -H in the ring may be replaced by -F, -Cl or -CN, and one or more -CH= in the ring may be replaced by -N=; Z N1 and Z N2 Each independently represents a single bond, -CO-O-, -O-CO-, -CH2O-, -OCH2-, -CH=CH-, -C≡C-, -CH2CH2-, -CF2CF2-, -(CH2)4-, -CF2O- or -OCF2-; L N1 and L N2 Each independently represents -H, an alkyl group containing 1 to 3 carbon atoms or a halogen; n N1 Represents 0, 1, 2, or 3, n N2 Represents 0 or 1, and 0≤n N1 +n N2 ≤3, when n N1 =2 or 3, the ring Can be the same or different, Z N1 Can be the same or different; R M1 and R M2 Each independently represents a straight or branched alkyl group containing 1 to 12 carbon atoms, One or more non-adjacent -CH2- in the linear or branched alkyl group containing 1 to 12 carbon atoms may be independently replaced by -CH=CH-, -C≡C-, -O-, -CO-, -CO-O- or -O-CO-; ring ring and ring Each independently expresses in One or more -CH2- in the ring may be replaced by -O-, one or more single bonds in the ring may be replaced by double bonds, At most one -H in may be replaced by halogen; Z M1 and Z M2 Each independently represents a single bond, -CO-O-, -O-CO-, -CH2O-, -OCH2-, -C≡C-, -CH=CH-, -CH2CH2- or -(CH2)4-; n M represents 0, 1, or 2, where n M =2, ring Can be the same or different, Z M2 may be the same or different; and the compound of the general formula F accounts for 4%-30% by weight of the liquid crystal composition, the polymerizable compound of the general formula RM accounts for 0.001%-5% by weight of the liquid crystal composition, the self-alignment agent of the general formula SA accounts for 0.001%-5% by weight of the liquid crystal composition, the compound of the general formula N accounts for 0.1%-70% by weight of the liquid crystal composition, and the compound of the general formula M accounts for 0.1%-70% by weight of the liquid crystal composition.

2. The liquid crystal composition according to claim 1, characterized in that: The polymerizable compound of the general formula RM is selected from the group consisting of: as well as in, X1-X 10 and X 12 Each independently represents -F, -Cl, -Sp3-P3, a linear alkyl or alkoxy group containing 1 to 5 carbon atoms, 3. The liquid crystal composition according to claim 1, characterized in that: The self-aligning agent of the general formula SA is selected from the group consisting of the following compounds: as well as in, LS 31 Indicates -F, -Cl, -CN, -NO2, -NCO, -NCS, -OCN, -SCN, -C(O)N(R S0 )2. -C(O)R S0 , a straight or branched alkyl group containing 1 to 12 carbon atoms, wherein one or more non-adjacent -CH2- in the straight-chain or branched alkyl group containing 1 to 12 carbon atoms can be independently replaced by -CH=CH-, -C≡C-, -O-, -CO-, -CO-O- or -O-CO-, and the straight-chain or branched alkyl group containing 1 to 12 carbon atoms, One or more -H in the above-mentioned may be independently replaced by -F, wherein R S0 represents a straight or branched chain alkyl group containing 1 to 12 carbon atoms; LS 21 Indicates -Sp 3 -P 2 or and Z 11 Represents -O-, -S-, -CO-, -CO-O-, -O-CO-, -O-CO-O-, -CH2O-, -OCH2-, -CH2S-, -SCH2-, -CF2O-, -OCF2-, -CF2S-, -SCF2-, -(CH2) d -, -CF2CH2-, -CH2CF2-, -(CF2) d -, -CH=CH-, -CF=CF-, -CH=CF-, -CF=CH-, -C≡C-, -CH=CH-CO-O-, -O-CO-CH=CH-, -CH2CH2-CO-O-, -O-CO-CH2CH2-, -CHR 1 -、-CR 1 R 2 - or a single bond, where R 1 and R 2 Each independently represents a linear or branched alkyl group containing 1 to 12 carbon atoms, and d represents an integer of 1-4.

4. The liquid crystal composition according to claim 1, characterized in that: The compound of formula N is selected from the group consisting of the following compounds: as well as 5. The liquid crystal composition according to claim 1, characterized in that: The compound of formula M is selected from the group consisting of the following compounds: as well as 6. A liquid crystal display device comprising the liquid crystal composition according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Liquid crystal compound and liquid crystal composition

    CN110527520A

  • Compound, liquid crystal composition and application thereof

    CN113277946A

  • Self-alignment agent compound and application thereof

    CN113563900A

  • Liquid crystal composition and liquid crystal display device thereof

    CN115216305A